PENGARUH MOTIVASI TERHADAP PRODUKTIVITAS KERJA PEGAWAI DINAS PERINDUSTRIAN DAN TENAGA KERJA KABUPATEN TEGAL - Hartanto Hartanto; Christina Amanda Savitri; Lady Olivia Mahardika (LP2M Universitas Bina Bangsa, 2022)
Civil Servants (PNS) are expected to have high motivation in doing their work and good quality of service to the community. From the data obtained related to the presence of employees which is one of the motivational factors, it is shown that there are still employees who come to work not on time. In addition, based on the Community Satisfaction Index (IKM) survey conducted by the author on the work productivity of employees of the Tegal Regency Industry and Manpower Office, an average number of 2.99 from a maximum value of 4 can be interpreted as the need for improvement in several aspects of service. This study aims to determine the influence of motivation on the work productivity of employees of the Tegal Regency Industry and Manpower Service. The respondents of this study were 44 people. This study is a quantitative study with saturated sampling. Data collection was carried out by distributing questionnaires through google forms to 44 respondents. The results of this study through a simple linear regression test were shown by the equation Y = 20.328 + 0.187X. This means that if X=0 then the value of Y=20.328 and is positive. The value of the regression coefficient X of 0.187 has the understanding that every 1% addition of the value of the Motivation variable (X), the value of the Work Productivity variable (Y) increases by 0.187. The result of the t test result, obtained the calculated t value = 2,342 > t table = 2.018 and the significance value of 0.024 < 0.05. Based on the results of the coefficient of determination test, an R square value of 0.115 was obtained. This means that the magnitude of the influence of the motivation variable on the work productivity variable is 11.5%. Thus, it is known that the high low work productivity at the Tegal Regency Industry and Manpower Office is influenced by motivation of 11.5%, the rest is influenced by other factors that are not included in this study